Analisis Pengaruh Tingkat Likuiditas Terhadap Profitabilitas Pada PT. PLN (Persero) Kabupaten Bulukumba - Fahira Fahira (Al-Kharaj: Journal of Islamic Economic and Business, 2019)
The main indicator of this research was how could the companies survive and develop, and the objective effort in increasing profitability. Labored between liquidity on one side and profitability on the other side is not contradictory and can achieve optimal profits without sacrificing company liquidity. This research aimd to determine the effects of liquidity as measuring using the current ratio (CR) on profitability as measuring by Return on Assets (ROA) at PT PLN (Persero) Bulukumba in the period of 2015 to 2017. This research employed quantitative research. Furthermore, the method of data analysis was using financial ratio analysis, simple regression analysis, t-test and coefficient of determination. The results of this research that was conducted at PT PLN (Persero) Bulukumba with employed data from 2015 until 2017: (1) The effect of liquidity on profitability showed a negative effect, (2) Current Ratio didn’t have a significant effect on Return on Assets.